Psychosocial characteristics of infertile couples: a study by the "Heidelberg Fertility Consultation Service" - Wischmann, Tewes; Stammer, Heike; Scherg, Horst; Gerhard, Ingrid; Verres, Rolf (Human reproduction, 2001)
BACKGROUND: The aim of the study was to identify differences in psychological characteristics between couples with fertility disorders, especially idiopathic infertility, and a representative sample. MATERIAL AND METHODS: A total of 564 couples was examined using psychological questionnaires pertaining to sociodemographic factors, motives for wanting a child, dimensions of life satisfaction and couple relationships, physical and psychic complaints, and a personality inventory. RESULTS: Specific to our sample was the high educational level of the couples, and the large number with idiopathic infertility (27% of all diagnoses). There were no remarkable differences in psychological variables between the infertile couples and a representative sample, except that the infertile women showed higher scores on the depression and anxiety scales. Couples with idiopathic infertility showed no remarkable differences in the questionnaire variables compared with couples with other medical diagnoses of infertility. CONCLUSIONS: A typical psychological profile for infertile couples could not be identified using standardized psychometric rating methods. This may be an effect of the specific characteristics of our sample. For some couples, the infertility crisis can be seen as a cumulative trauma, which indicates that these couples have a marked need for infertility counselling.
Gesehen am 17.02.2021